The Mongolian economy : a manual of applied economics for a country in transition - Nixson, F. I. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2000)
This book focuses on the experience of the development of a dynamic private enterprise sector in developing countries and transactional economies. The discussion considers privatisation,foreign investmena and the ownership of small and medium sized fims in different countries.
Includes bibliographical references and index.
aia 18/09/13
Loan
Keywords: Mongolia -- Economic policy; Mongolia -- Economic conditions